2013
DOI: 10.1002/pd.4141
|View full text |Cite
|
Sign up to set email alerts
|

Association between first‐trimester maternal serum pregnancy‐associated plasma protein‐A and obstetric complications

Abstract: Maternal serum PAPP-A levels are lower in women who develop preeclampsia, those with SGA fetus and those who deliver preterm. However, on its own, maternal serum PAPP-A performs poorly (OR for PE between 1.76 and 2.41 with the lower percentile of PAPP-A) as a screening test for these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 57 publications
7
40
1
2
Order By: Relevance
“…interleukin-1β (IL-1β) in the first trimester of pregnancy as predictive markers, but these molecules showed poor to moderate predictive value for PE [25]. [28].…”
Section: Existing Prognostic Biomarkers and Need For New Biomarkersmentioning
confidence: 99%
“…interleukin-1β (IL-1β) in the first trimester of pregnancy as predictive markers, but these molecules showed poor to moderate predictive value for PE [25]. [28].…”
Section: Existing Prognostic Biomarkers and Need For New Biomarkersmentioning
confidence: 99%
“…IUGR, PTD and GD, we failed to demonstrate any significant differences between the two groups, even if an increase of low PAPP-A levels in these diseases without reaching statistical significance was shown. However, using a PAPP-A MoM value similar to ours, other researchers [1,2] found significant differences in pre-term births and IUGR, with an OR value varying from 3 to 4. Also for GD, first-trimester PAPP-A values were significantly lower in women who subsequently developed GD, compared to a control group [3]; furthermore, serum PAPP-A concentrations correlated independently and inversely with subsequent GD.…”
Section: Discussionmentioning
confidence: 61%
“…At similar MoM cutoff values, the risk of GH and PE was slightly increased in our work compared to that of Dugoff et al [2]: OR 2.1 vs. 1.64 and 2.5 vs. 1.79, respectively. In a recent study by D'Antonio et al [1], in which 296 PE women were evaluated, the PAPP-A level was <3rd centile which corresponds to 0.34 MoM, the OR calculated was 2.2 which is not different from ours (OR 2.5), but if only the early PE was considered the OR reached 9.4, suggesting the importance of this marker for the most severe cases. The same group has recently demonstrated that first-trimester PAPP-A MoM values were directly correlated with gestational age at delivery [7].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The use of maternal serum screening solely to predict and prevent these outcomes has not been supported due to overall low sensitivity and high false-positive rates [11,12]. D'Antonio et al [13] reported that maternal serum PAPP-A performs poorly as a screening test for PT, SGA and preeclampsia. The ROC analysis showed that the AUC under the ROC curve in this analysis for PAPP-A to predict LBW and PT was 0.7 and 0.68, respectively, indicating that it has a ''fair'' predictive accuracy [14].…”
Section: Discussionmentioning
confidence: 99%